HUBUNGAN MINDFULNESS IN COMMUNICATION DAN VOICE BEHAVIOR PADA KARYAWAN OPERASIONAL INDUSTRI FOOD & BEVERAGE DI JAKARTA - Salvezza, Sheila; Subroto, Untung (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Communication problems that frequently occur in the workplace can be addressed through mindfulness, particularly mindfulness in communication, which refers to an individual’s ability to be fully present, open, and to respond calmly during the communication process. One aspect of workplace behavior related to mindfulness in communication is voice behavior, defined as employees’ tendency to express ideas or suggestions aimed at encouraging organizational improvement or change. This study aimed to examine whether there is a relationship between mindfulness in communication and voice behavior among employees in the Food & Beverage (F&B) industry in Jakarta. This study employed a non-experimental quantitative approach using purposive sampling as the data collection technique. The instruments used were the Mindfulness in Communication Scale and the Voice Behavior Scale. A total of 246 participants were involved, consisting of employees who were currently or had previously worked as operational employees in the F&B industry in Jakarta, worked in team-based F&B companies rather than individual enterprises, and had a minimum of six months of work experience. The results of the analysis indicated that mindfulness in communication had a positive correlation with voice behavior. These results suggest that higher levels of mindfulness in communication are associated with higher levels of voice behavior among operational employees in the F&B industry in Jakarta. Based on these findings, organizations may develop programs focused on enhancing mindfulness in communication and voice behavior to support better communication and increase employee contributions within the organization. ABSTRAK Permasalahan komunikasi yang sering terjadi di tempat kerja dapat diatasi dengan mindfulness, khususnya mindfulness in communication yang merupakan kemampuan individu untuk hadir secara utuh, terbuka, serta merespons dengan tenang dalam proses komunikasi. Salah satu aspek perilaku di tempat kerja yang berkaitan dengan mindfulness in communication adalah voice behavior, yaitu kecenderungan karyawan untuk menyampaikan ide atau masukan yang bertujuan untuk mendorong perubahan atau perbaikan organisasi. Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara mindfulness in communication dan voice behavior pada karyawan industri Food & Beverage (F&B) di Jakarta. Penelitian ini menggunakan pendekatan kuantitatif non-eksperimental dengan teknik pengambilan data purposive sampling. Alat ukur yang digunakan adalah Mindfulness in Communication Scale dan Voice Behavior Scale. Partisipan berjumlah 246 karyawan dengan karakteristik sedang atau pernah bekerja sebagai karyawan operasional di industri F&B di Jakarta, bekerja di perusahaan F&B berbasis tim dan bukan usaha perseorangan, serta memiliki pengalaman kerja minimal enam bulan. Hasil analisis menunjukkan bahwa mindfulness in communication memiliki korelasi positif dengan voice behavior. Hasil tersebut dapat diartikan bahwa semakin tinggi tingkat mindfulness in communication, maka semakin tinggi pula tingkat voice behavior pada karyawan operasional di industri F&B di Jakarta. Berdasarkan hasil penelitian ini, perusahaan dapat mengembangkan program yang berfokus pada peningkatan mindfulness in communication dan voice behavior untuk mendukung komunikasi yang lebih baik dan meningkatkan kontribusi karyawan dalam organisasi.